The Effect Of Tree Induce Suction On Slope Stabilization Analysis - Wan Faizal, Wan Ishak; N., Ali; Asiah, Kassim (Penerbit UMP, 2013)
This research was conducted to study the effect of active root zone related to slope stabilization. The matric suction produced by mature tree was determined during high and moderated intensity of rainfall event condition, which related to significant changes on stability of the slope. The increasing of soil moisture and porewater pressure can significantly reduce shear strength of soil which lead to shallow slope failure. This study determined the active root zone of the tree near the toe of the slope which suctions have been generated within this section. In related with this, the effect it only focusing on hydrological aspect with soil moisture pattern near vicinity of the tree. The field monitoring result showed that there was a substantially increase in soil suction near the vicinity of tree. The effect of tree water uptake on soil suction profiles was applied for slope stability analysis. The findings indicate that the influence of rain fall event can cause variation to soil suction that is related to factor of safety. Furthermore, water uptake from root activity created dry condition that substantially increased the factor of safety against slope failure has improved up to 45.54%